Role of forest on Carbon Sequestration in Soils of Joida and Karwar Taluka of Uttara Kannada District - Koppad, A. G.; Tikhile, Pavan (Indian Forester, 2014)
The study was conducted in Joida and Karwar talukas of Uttara Kannada district, Karnataka, to assess the effect of land use land cover on carbon sequestration in soil. The IRS P6 LISS-III imageries were used for generating of LULC thematic map of study region and are classified using ERDAS-2011 software with ground truth data collected through GPS. The land use classes viz., dense forest, agriculture land and barren land were identified. The soil samples up to one meter depth were collected from each land use system and SOC was estimated. The result indicated that the soil organic carbon in different land uses were significantly different. The total SOC in Joida and Karwar taluka was 20.69 and 7.42 million tons respectively. The average SOC in Joida and Karwar soil was 83.59 and 85.06 t/ha respectively. The carbon mitigation potential in dense forest soil was 2.13 and 2.28 times more in Joida and Karwar taluka respectively as compared to Agriculture soil. The forest cover helps sequester more carbon in soils and reduce green house gases from atmospheres.